MENGGAGAS INDONESIA SEBAGAI NEGARA HUKUM YANG MEMBAHAGIAKAN RAKYATNYA - Hamzani, Achmad Irwan (Yustisia, 2014)
The development of the concept of state law is a product of history. Formulation of understanding continues to evolve to follow the historical development of society in the state, although in practice the discussion refers to the concept of the modern state of the mainstream since the 19th century; Continental European Rechtstaats concept, and Anglo-Saxon with the concept of Rule of Law. Each country has its own style. The concept of state law in one country can not be forced into other countries. Indonesia has the Pancasila ideology that by applying them consistently, so it can become law states that happy people.